2008
DOI: 10.1166/jnn.2008.ic48
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide Thin Films Deposited by Plasma Enhanced Atomic Layer Deposition for OLED Passivation

Abstract: Plasma enhanced atomic layer deposition (PEALD) of titanium dioxide thin films was conducted using Tetrakis dimethylamino titanium (TDMATi) and an oxygen plasma on a polyethersulfon (PES) substrate at a deposition temperature of 90 degrees C. The effects of the induced plasma power on passivation properties were investigated according to film thickness. The growth rate of the titanium dioxide film was 0.8 A/cycle, and the water vapor transmission rate (WTVR) for a 80 nm titanium dioxide film was 0.023 g/m2 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…By the aforementioned results it is concluded that, also under mild plasma conditions, ions have a strong impact on the film crystallinity and GPC during plasma ALD of TiO 2 . Since the flux and energy of ions is dependent on the plasma source design and plasma conditions employed, this strong impact of ions could (partly) explain the limited process reproducibility and large spread in GPC values reported for TiO 2 in the literature, , which appears to be a long-standing issue. To better control the growth of TiO 2 thin films by plasma ALD, it is therefore important to gain detailed information on the influence of ions under various conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the aforementioned results it is concluded that, also under mild plasma conditions, ions have a strong impact on the film crystallinity and GPC during plasma ALD of TiO 2 . Since the flux and energy of ions is dependent on the plasma source design and plasma conditions employed, this strong impact of ions could (partly) explain the limited process reproducibility and large spread in GPC values reported for TiO 2 in the literature, , which appears to be a long-standing issue. To better control the growth of TiO 2 thin films by plasma ALD, it is therefore important to gain detailed information on the influence of ions under various conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the growth per cycle (GPC) is observed to be highly susceptible to the influence of (low-energy) ions. This can be an important factor behind the large spread in GPC values reported in the literature , for this process (see the Supporting Information). Therefore, detailed information on the influence of ions may be essential for improving the limited reproducibility of plasma ALD of TiO 2 in between labs and ALD tools, which appears to be a long-standing issue.…”
Section: Introductionmentioning
confidence: 98%
“…TiO 2 thin film was deposited by PEALD on PES substrate at the lower temperature of 90 °C and the OLEDs coated with TiO 2 thin film maintained at 52.5% of the initial luminance after 90 h aging (Table 2). [ 174 ] Besides, silicon‐based inorganic monolayer film could be deposited by using PECVD which is also performed as encapsulation film for OLEDs. [ 175 ] Si‐based inorganic single layer usually shows WVTR value of 0.005 g m −2 day −1 , which is sufficient for the encapsulation of OLEDs.…”
Section: Encapsulation Classification and Techniquementioning
confidence: 99%
“…In particular, Al 2 O 3 ALD has been employed to passivate or encapsulate OLED and organic solar cells to prevent H 2 O permeation [70,[79][80][81][82]. Many researchers have demonstrated the gas diffusion barrier films on polymer as summarized in table 2 [79][80][81][82][83][84][85]. At the beginning, plasma-enhanced atomic layer deposition (PEALD), enabling deposition at low temperature due to high energetic radicals, has been used to deposit the Al 2 O 3 thin film below 100 • C [79].…”
Section: Atomic Layer Deposition/molecular Layer Deposition Technologymentioning
confidence: 99%